First documented case of pulmonary alveolar proteinosis with atopy presenting secondary to CSFR2B mutation - KIYAN, GÜRSU (My University, 2022)
Pulmonary alveolar proteinosis (PAP) is a rare lung disorder in which surfactant-derived lipoproteins accumulate excessively within pulmonary alveoli, causing severe respiratory distress. It is essential to gain a better understanding of the signs to clinically diagnose PAP and include PAP among the differential diagnoses of interstitial pulmonary diseases or other diseases with similar manifestations. We describe a 2.5-year patient with atopy who presented with pulmonary infiltration, recurrent wheezing, and cough despite steroid and salbutamol administration via inhalation. High-resolution computed tomography revealed crazy-paving patterns in both lungs, suggesting PAP. An open lung biopsy revealed intra-alveolar granular amphophilic material, which was strongly positive on periodic acid-Schiff staining. The results of pulmonary-associated surfactant protein B and C gene analyses were normal. However, granulocyte-macrophage colony-stimulating factor receptor beta-protein was not detected in leucocytes, and a novel mutation was identified in the CSF2RB gene. The patient was diagnosed with PAP and treated with whole-lung lavage. Key Words: Pulmonary alveolar proteinosis, Child, Atopy, Wheezing.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Pulmonary alveolar proteinosis; Child; Atopy; Wheezing